KOMPETENSI PROFESIONAL GURU PAI DI MADRASAH ALIYAH NURUL HUDA SUKARAJA OKU TIMUR - Slamet Pujiono (Jurnal Al-Hikmah, 2020)
Abstract Teacher professional competence is the ability to master learning material widely and in depth that Teacher professional competence is the ability to master learning material widely and in depth that allows guiding students to meet the competency standards set in national standards, to improve professional competence, the teacher must be able to master science according to the field, manage teaching and learning programs, manage classes, develop professionalism in a sustainable manner and use learning media / technology. Based on this, the purpose of this study was to determine the professional competence of Islamic Religious Education teachers in Madrasah Aliyah Nurul Huda Sukaraja, East OKU, South Sumatra. This research is included in the type of qualitative field research, data collection techniques in this study using several methods, namely the observation method, the interview method and the documentation method. While data analysis uses an interactive analysis model that is data reduction, data presentation, verification and conclusion drawing. Based on the results of research on the professional competence of Islamic Religious Education (PAI) teachers in the learning process in Madrasah Aliyah Nurul Huda Sukaraja, East OKU, South Sumatra, it can be seen that all professional competencies have been able to run optimally although there is still a need to increase in all indicators. Keywords: Teacher Professional Competencies, Islamic Religious Education